2015
DOI: 10.3892/mmr.2015.4316
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cadmium on the expression levels of interleukin-1α and interleukin-10 cytokines in human lung cells

Abstract: Cadmium is an environmentally hazardous metal, which causes toxicity in humans. Inhalation of cigarette smoke and industrial fumes containing cadmium are sources of cadmium exposure. It is responsible for the malfunction of various organs, leading to disease particularly in the lungs, liver and kidneys. In the present study, the effect of cadmium chloride (CdCl2) on cell viability, and the expression levels of interleukin (IL)-1α and IL-10 cytokines at various concentrations and incubation durations were asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 32 publications
0
15
1
Order By: Relevance
“…Notably, we have previously shown that IL-1β is released from mouse macrophage (RAW264.7) upon exposure to different types and sizes of silica particles [12]. IL-1α is an alarmin, known to be released from both macrophages [60] as well as epithelial cells upon exposure to various agents [61,62]. Also IL-1β is released from both macrophages and epithelial lung cells upon exposure to silica particles [12,18].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, we have previously shown that IL-1β is released from mouse macrophage (RAW264.7) upon exposure to different types and sizes of silica particles [12]. IL-1α is an alarmin, known to be released from both macrophages [60] as well as epithelial cells upon exposure to various agents [61,62]. Also IL-1β is released from both macrophages and epithelial lung cells upon exposure to silica particles [12,18].…”
Section: Discussionmentioning
confidence: 99%
“…Serum levels of interleukin 1 beta (IL-1 β), tumor necrosis factor alpha (TNF-α), and interleukin 10 (IL-10) were determined by using ELISA kits according to methods described by Vidal et al (2000), Brynskov et al (2002), and Odewumi et al (2015), respectively [ 37 , 38 , 39 ].…”
Section: Methodsmentioning
confidence: 99%
“…Determination of serum level of interleukin 1 beta (IL-1β) using kit from (Bio-Diagnostics Ltd, Egypt) (Catalog No. IL 1234 ) according to Vidal et al (2000), tumor necrosis factor alpha (TNF-α) according to Brynskov et al (2002) using kit from (Bio-Diagnostics Ltd, Egypt) (Catalog No: TF 1691), and Serum concentration of interleukin-10 (IL-10)by using kit from (Bio-Diagnostics Ltd, Egypt) (Catalog No: IL 2341) according to methods described by Odewumi et al (2015).…”
Section: Methodsmentioning
confidence: 99%